PCR Analysis of expR Gene Regulating Biosynthesis of Exopolysaccharides in Sinorhizobium meliloti - Sorroche, Fernando Guido (2012)
Exopolysaccharide (EPS) production by the rhizobacterium Sinorhizobium meliloti is essential for root nodule formation on its legume host (alfalfa), and for establishment of a nitrogen-fixing symbiosis between the two partners. Production of EPS II (galactoglucan) by certain S. meliloti strains results in a mucoid colony phenotype. Other strains that are unable to produce EPS II display a dry phenotype, due to the presence of an insertion element in the gene expR, a key regulator involved in many important cellular processes, including production of low-molecular-weight EPS II. We describe a series of three programmed undergraduate biochemistry laboratory classes teaching PCR and electrophoresis procedures to detect non-functional expR loci in S. meliloti.